Physiological responses to capture and transport in southern white rhinoceros (Ceratotherium simum simum) and southern-central black rhinoceros (Diceros bicornis minor) - Meyer, Leith Carl Rodney (University of Pretoria, 2024)
Thesis (PhD)--University of Pretoria, 2019.